Determinants of Organic Food Consumption in Narrowing the Green Gap - Brahim Chekima; Mohamed Bouteraa; Rudy Ansar; Suddin Lada; Lim; Elhachemi Tamma; Azaze Azizi Abdul Adis; Khadidja Chekima (MDPI, 2023)
Understanding and recognizing environmentally friendly behaviour are vital in achieving the Sustainability Development Goals and driving the economy for countries and producers of environmentally-friendly goods. Nevertheless, various stakeholders have expressed concern about the existing green gap, which greatly hinders their marketing efforts. This situation persists as mainstream research investigates people’s purchasing intentions, under the notion that the intention to perform a specific behaviour would generally predict the actual behaviour. The key argument of this study is that examining the actual consumption behaviour of organic foods is the ideal approach towards investigating purchase intention drivers as a proxy for consumption. In response to the green gap, the theory of planned behaviour is expanded by including the dimension of temporal orientation, i.e., a future orientation that has an influential but unrecognised effect on many human behaviours. In contrast to the prevalent operationalization of attitude, the term is defined as a product-specific attitude which is markedly dissimilar to the environmental attitude in its orientations. The Partial Least Squares Structural Equation Modeling technique was used to analyse the research model. The findings indicate that while product-specific attitudes and perceived availability positively affect organic food consumption, subjective norms do not. Additionally, the data implies that product specific attitudes are stronger when future orientation is high.